Chronos & Kairos : Die Zeit in der Zeitgenössischen Kunst. - Block, René; Busche, Ernst A.; Butin, Hubertus; Christiansen, Henning; Glaser, Martin; Gosewitz, Ludwig; Hasegawa, Yuko; Heinz, Marianne; Lange, Christoph; Müller, Vanessa Joan (Kassel : Museum Fridericianum, 1999)
Almond, Darren ; Antoni, Janine ; Apple, Billy ; Ben ; Beuys, Joseph ; Biava, Maura ; Bloom, Barbara ; Böhmler, Claus ; Brecht, George ; Brehmer, Klaus-Peter ; Broodthaers, Marcel ; Cage, John ; Christiansen, Henning ; Darboven, Hanne ; Dege, Martin ; Dibbets, Jan ; Duchamp, Marcel ; Eichhorn, Maria ; Erkmen, Ayse ; Feldmann, Hans-Peter ; Filliou, Robert ; Fischer, Nina & Sani, Maroan el ; Gosewitz, Ludwig ; Gröting, Asta ; Higgins, Dick ; Hödicke, Karl Horst ; Jankowski, Christian ; Kabakov, Ilya ; Kaprow, Allan ; Kawara, On ; Köpcke, Arthur ; Kopystiansky, Svetlana & Igor ; Kosuth, Joseph ; Kozlowski, Jaroslaw ; Krumwiede, Christiane ; Kubota, Shigeko ; Laessing, Nick ; Maciunas, George ; Man Ray ; Metzel, Olaf ; Miyajima, Tatsuo ; Mori, Mariko ; Nauman, Bruce ; Ono, Yoko ; Paik, Nam June ; Riddle, James ; Roth, Dieter ; Ruff, Thomas ; Rühm, Gerhard ; Sarkis ; Schmit, Tomas ; Streeruwitz, Marianne ; Taylor-Wood, Sam ; Tot, Endre ; Trockel, Rosemarie ; Unsworth, Ken ; Val, Olaf ; Vostell, Wolf ; Warhol, Andy ; van Warmerdam, Marijke ; Watts, Robert ; Weiner, Lawrence ; Williams, Emmett ; Wirkkala, Maaria ; Young, La Monte ; Zazeela, Marian
Duits
Chronos & Kairos : Die Zeit in der zeitgenössischen Kunst, Museum Fridericianum, Kassel, 5. September bis 7. November 1999
kunstcatalogus